2016
DOI: 10.1111/tri.12820
|View full text |Cite
|
Sign up to set email alerts
|

The association between killer-cell immunoglobulin-like receptor (KIR) and KIR ligand genotypes and the likelihood of BK virus replication after kidney transplantation

Abstract: BK virus is a common opportunistic post-transplantation viral infection. Although some risk factors have been studied in this context, the contribution of NK cells has not been assessed in detail. In a group of kidney transplant recipients, we studied the association between (i) the likelihood of BK virus replication during the two-year period after kidney transplantation and (ii) the genotypes of the killer cell immunoglobulin-like receptor (KIR) repertoire and their human leukocyte antigen (HLA) ligands. Oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…An allogeneic recognition system consisting of KIR and human leukocyte antigen C (HLA-C) can participate in human immune response under the regulation of NK cells [35]. A number of studies have shown that KIRs are significantly associated with transplant rejection, mainly related to their immune processes and associated with a variety of immune diseases, such as kidney transplantation [36,37], ankylosing spondylitis [38], and psoriatic [39,40]. Previous studies have shown that women with recurrent spontaneous abortion lack inhibitory KIRs (2DL1, 2DL2, and 2DL3) and cannot inhibit the killing activity of NK cells, leading to miscarriage [41].…”
Section: Discussionmentioning
confidence: 99%
“…An allogeneic recognition system consisting of KIR and human leukocyte antigen C (HLA-C) can participate in human immune response under the regulation of NK cells [35]. A number of studies have shown that KIRs are significantly associated with transplant rejection, mainly related to their immune processes and associated with a variety of immune diseases, such as kidney transplantation [36,37], ankylosing spondylitis [38], and psoriatic [39,40]. Previous studies have shown that women with recurrent spontaneous abortion lack inhibitory KIRs (2DL1, 2DL2, and 2DL3) and cannot inhibit the killing activity of NK cells, leading to miscarriage [41].…”
Section: Discussionmentioning
confidence: 99%
“…The HLA molecules interact with KIRs so that HLA molecules act as ligands and KIRs on the NK cell surface act as receptors (Brochot et al 2016). The degree of the contact between KIRs and HLA molecules controls whether activating or inhibitory signals are transmitted, which determines NK cell function (Tuttolomondo et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear which biological mechanism is underlying these findings for HCMV seronegative patients at the time of transplantation and whether the lack of T or NK cell memory in this specific group in combination with immunosuppression of T cell responses during the initial stage of infection plays a role. A protective role for KIR B haplotypes has also been observed for Varicella zoster (78) and BK virus (79) though two other studies did not find a significant impact of KIR haplotypes on BK virus (78,80). The impact of KIR repertoires on other viral infections is not very well studied.…”
Section: Impact Of Kir-hla Class I Interaction On Kidney Transplantation Outcomementioning
confidence: 99%